Ethylene oligomerization on nickel catalysts on a solid acid support: From New mechanistic insights to tunable bifunctionality - Koninckx, Elsa; Mendes, Pedro S.F.; Thybaut, Joris W.; Broadbelt, Linda J. (Applied catalysis. A, General, 2021)
[Display omitted] •Addresses gaps in review literature by proposing a comprehensive mechanistic view for heterogenous nickel-acid catalysts.•Highlights relevant conditions to steer product distributions of ethylene oligomerization towards desirable products.•Focuses on environmentally-friendly and flexlble catalysts to produce a range of products for ever-changing market demands. Light alkene oligomerization on heterogeneous acidic catalysts is widely and successfully used in current commercial processes. However, ethylene oligomerization remains inefficient due to ethylene’s inability to form reaction intermediates to a sufficient extent on acid sites. Adding Ni(II) on solid acids can more efficiently catalyze ethylene oligomerization and selectively produce butenes to fuel range products. The review proposes a complete and detailed mechanism of heterogenous Ni-catalyzed oligomerization, whose structures are supported by combining various studies throughout recent literature, and focuses on the bifunctional effects of the nickel and acid sites on ethylene oligomerization. Using experiments, first-principles calculations, and kinetic modeling, Ni2+ has been shown to selectively oligomerize ethylene to light, linear alkenes via the Cossee-Arlman mechanism, while Brønsted H+ sites catalyze further alkylation, cracking, and isomerization reactions. The effects of reaction conditions and catalyst properties on selectivity and activity for oligomerization are systematically discussed. Tuning the relative nickel-to-acid site ratio and the framework support can allow for an optimal catalyst design directed towards desirable products.